Old treatments for new genetic conditions: Sirolimus therapy in a child affected by mosaic overgrowth with fibroadipose hyperplasia. Issue 1 (22nd April 2019) - Leoni, Chiara; Onesimo, Roberta; Resta, Nicoletta; Patti, Maria L.; De Santis, Rita; Bagnulo, Rosanna; Russo, Luca; Manfredi, Riccardo; Genuardi, Maurizio; Zampino, Giuseppe
Abstract : PIK3CA‐related overgrowth spectrum (PROS) are overgrowth diseases involving mesenchymal tissues caused by postzygotic variants in the PIK3CA gene. Fibro‐Adipose hyperplasia or Overgrowth (FAO) belongs to PROS. We reported the beneficial effect of oral low‐dose sirolimus therapy in a child affected by progressive FAO in term of stabilization of the disease, good tolerability, and easy management.